A Proteomic Comparison of Formalin-Fixed Paraffin-Embedded Pancreatic Tissue from Autoimmune Pancreatitis, Chronic Pancreatitis, and Pancreatic Cancer - Paulo, Joao A; Kadiyala, Vivek; Brizard, Scott; Banks, Peter A; Steen, Hanno; Conwell, Darwin L (JOP. Journal of the Pancreas, 2013)
Content Formalin-fixed paraffin-embedded (FFPE) tissue is a standard for specimen preservation, and as such FFPE tissue banks are an untapped resource of histologically-characterized specimens for retrospective biomarker investigation for pancreatic disease. Objectives We use liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) to compare FFPE specimens from three different diseases of the exocrine pancreas. Design We investigated the proteomic profile of FFPE pancreatic tissue from 9 archived specimens that were histologically classified as: autoimmune pancreatitis (n=3), chronic pancreatitis (n=3), and pancreatic cancer (n=3), using LC-MS/MS. Setting This is a proteomic analysis experiment of FFPE pancreatic tissue in an academic center. Patients FFPE tissue specimens were provided by Dana-Farber/Harvard Cancer Center (Boston, MA, USA). Interventions FFPE tissue specimens were collected via routine surgical resection procedures. Main outcome measures We compared proteins identified from chronic pancreatitis, autoimmune pancreatitis, and pancreatic cancer FFPE pancreatic tissue. Results We identified 386 non-redundant proteins from 9 specimens. Following our filtering criteria, 73, 29, and 53 proteins were identified exclusively in autoimmune pancreatitis, chronic pancreatitis, and pancreatic cancer specimens, respectively. Conclusions We report that differentially-expressed proteins can be identified among FFPE tissues specimens originating from individuals with different histological diagnoses. These proteins merit further confirmation with a greater number of specimens and orthogonal validation, such as immunohistochemistry. The mass spectrometry-based methodology used herein has the potential to enhance diagnostic biomarker and therapeutic target discovery, further advancing pancreatic research. Image: Distribution of proteins among the AIP, CP, and PC cohorts.